The Integration of Nurse Training into the University of Swaziland and its Impact on the Professionalisation of Nursing, 1980s-2007 - Dlamini, Shokahle R. (African historical review, 2024)
The turn of the twentieth century witnessed the onset of a discussion about how to properly educate a nurse. This discussion highlighted the irrelevance of the hospital-based nurse training model, ultimately pushing nurse training to colleges associated with universities. Scholarship on the transition from hospital to university-based nurse training in southern Africa is thin. In Swaziland (now Eswatini), the affiliation of nursing colleges with the University of Swaziland (UNISWA) occurred in 1989. Integrating nurse training into UNISWA was an impetus for major shifts in nurse education in the territory, one of which was the professionalisation of nursing as a career. Profound as this development was, nothing has been written about it. Drawing from a wide range of sources, this article argues that the integration of nurse training into UNISWA was a desirable transformation in nurse education which enhanced the quality of nurse care service provision and professionalised nursing. The article provides the contextual background prior to the integration of nurse training into UNISWA for us to understand how nurse training was carried out in the period up to 1989. It discusses factors which facilitated the transition. It also examines this transition and explores its impact on the professionalisation of nurse training in Swaziland.